Biofunctionalized Titanium Dioxide Nanoparticles with Bovine Serum Albumin for Targeted Cytotoxicity in MCF-7 Breast Cancer Cells - Rahujo, Sanam; Talpur, Farah Naz; Laghari, Abdul Qadeer; Mert, Olcay; Afridi, Hassan Imran; Ali, Zafar; Razzaque, Noshad; Chandio, Imamdin; Zaman, Noor; Abro, Masroor (Universitas Gadjah Mada, 2026)
The titanium dioxide nanoparticles (TiO2NPs) were synthesized and functionalized with bovine serum albumin (BSA) to yield TiO2@BSA nanocomposites for targeted drug delivery. The chemotherapeutic drug vinorelbine (VRL), used for non-small cell lung and breast cancer, was loaded into the nanocomposites by a cost-efficient sol-gel method. The UV-vis spectrum exhibited an absorption peak at 361 nm, confirming the formation of TiO2 NPs. In the FTIR spectrum, the grafting of BSA was indicated by specific band shifts. XRD and FESEM revealed well-dispersed spherical particles with an average crystallite size of ⁓20 nm, and EDX confirmed elemental composition. The zeta potential of −29 mV indicated colloidal stability with a drug loading efficiency of 62%. In vitro release studies demonstrated pH-responsive behavior, with 98% cumulative release at an acidic pH (5.5) compared to 20% at physiological pH (7.4), indicating the suitability of this formulation for tumor-targeted delivery. Higuchi and Korsmeyer-Peppas models were used for the kinetics study, indicating that the mechanism was controlled by diffusion and swelling. Cytotoxicity evaluation via MTT assay showed enhanced uptake and anticancer activity of VRL-loaded TiO2@BSANPs against MCF-7 cells compared with free VRL. These results suggest TiO2@BSA nanocarriers as efficient, stable, and selective platforms for cancer therapy.